Análise de procedimentos pós-colheita do fruto da Macaúba (Acrocomia aculeata) e refino do óleo da polpa - Lorena Aires Lombardi Queiroz (2016)
The use of vegetable oils has been increasing throughout the world and currently their market is determined not only by the use for food purposes, and the production of pharmaceuticals and lubricants, as well as for the production of biodiesel. Brazil has an enormous diversity of species of oil plants of which can be extracted oils, and among these, Macauba Palm (Acrocomia aculeata) can be highlighted, a typical species of the Brazilian cerrado, which produces a fruit that can be used as source vegetable oil with high added value. All parts of the fruit can be used, however the economically more representative product is oil extracted from the pulp and kernel. Macauba pulp oil has similar applications to those obtained by other oilseeds, However, the limiting factors are the post-harvest and oil extraction, which is based on adapted to other oil technologies. Considering the assessment of fresh fruit (newly fallen) and the period of 30 day, the results of the analyzes of three consecutive harvests indicated that if the objective is to preserve the Macauba frutis, so that the pulp remains with lower acidity, the recommended treatment is washing with water followed by immersion in chlorinated solution 2 % and further drying in an oven at 60 ° C for 24 h. However, this treatment was not sufficient to ensure that the oil produced from this pulp had acidity index less than 4.0 mg KOH / g, limit established by ANVISA. Thus, to meet this need it is recommends that the processing is performed as soon as possible after harvest. Considering the evaluation of fruits collected and kept attached to the bunch during the entire release period of the fruit, the results of the evaluation at every 3 or 4 days, showed a continuous increase in titratable acidity of the pulp of 0.85 to 10.64% to the 36th day period, while the acidity index of the pulp oil resulted in values up to 1.58 mg KOH / g for 19 days and after that to variable values of 3.36 to 24.28 mg KOH / g. Simultaneously it was detected an increase in the oil content of the fruits kept the bunch to values of 43.43% to 52.94% (dry basis) in 36 days. After 19 days, the value was 50.71%. These results suggest that the fruit after harvest may be stored in the bunch maintained for about 20 days, providing characteristics desirable in higher oil content and with a still low acid number. The evaluation of the refining process for pulp oil with an initial acid value of 4.1 mg KOH /g, included the processes of degumming, neutralization and the clarification by two alternative processes. Firstly, one conventional adsorption process with commercial land. Secondly, one process proposed by this work, involving the use of land mixed with the activated carbon obtained from the endocarp of the Macauba fruit. The pulp oil refining process was efficient in the removal of free fatty acids, with values below 0.29 mg KOH/g. Further, the use of acommercial adsorbent mixture and activated carbon from the Macauba endocarp promoted a greater bleaching capacity and phosphorus removal compared to using only commercial earth.